Stepping up science-policy engagement to tackle environmental change: Methods and examples for achieving policy impact - Dinesh, Dhanush; Downing, Clare (2019)
In the context of rapid and unprecedented environmental change, there is growing emphasis amongst the scientific community to engage in policy processes and realise societal outcomes in addition to generating new knowledge. But, how can science-policy engagement efforts be delivered? What are the methods and tools? What are common challenges which need to be addressed? To address these questions, we provide insights and examples of the methods of science-policy engagement by researchers at the Environmental Change Institute, University of Oxford. These practical insights aim to provide guidance for others in the research community to deliver their ambitions to engage in policy processes and generate societal outcomes.